2010
DOI: 10.1186/1472-6963-10-323
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of advisory committees and public involvement to large studies: case study

Abstract: BackgroundMany large studies have complex advisory committee structures, yet there is no empirical evidence regarding their optimal composition, scope and contribution. The aim of this study was to inform the committee and advice infrastructure for future research studies.MethodsIn the context of a five-year study funded by the UK National Institute for Health Research, three advisory committees were formed. In addition, advice was obtained from individual experts. All recommendations received in the start-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…For example, relationships of trust are needed between scientific researchers and experts by experience (Slade et al 2010). Such relationships evolve over time, and need to be based on genuine partnership in which the sometimes difficult issues of power imbalances are acknowledged.…”
Section: Can Recovery Be Scientifically Investigated?mentioning
confidence: 99%
“…For example, relationships of trust are needed between scientific researchers and experts by experience (Slade et al 2010). Such relationships evolve over time, and need to be based on genuine partnership in which the sometimes difficult issues of power imbalances are acknowledged.…”
Section: Can Recovery Be Scientifically Investigated?mentioning
confidence: 99%
“…This critical friendship approach to PPI has been shown in another study to improve research quality. 196 l There was no governance requirement to go to an ethics committee for PPI. However, we felt it was important to be mindful of potential current vulnerabilities within the PPI study group.…”
Section: Three Stages Followedmentioning
confidence: 99%
“…In our formal evaluation of the impact of the LEAP on REFOCUS (Slade et al, 2010), we identified the costs and benefits for study quality. Summarising the benefits, the study design was improved through a closer match with the community's needs and interests.…”
Section: Discussionmentioning
confidence: 99%
“…This was implemented for the first 7 months of the study and then published (Slade et al, 2010), but then had to be discontinued.…”
Section: User Involvement Was Very Much On the Terms Of The Refocus Pmentioning
confidence: 99%
See 1 more Smart Citation